Pengaruh Celebrity Endorser dan Brand Image terhadap Keputusan Pembelian Produk Fashion pada Media Sosial Instagram - Allicya Willma Hillary (Penerbit Yayasan Daarul Huda Kruengmane, 2023)
In the modern era, the increase in fashion business people in Indonesia who use Instagram as a means of promotion raises a lot of competition. Thus, business people must be careful in choosing celebrity endorsers to attract consumers. One celebrity endorser who is on the rise in popularity due to the uniqueness of his endorsement content is Fadil Jaidi. This makes an Indonesian fashion brand called M231 entrust Fadil Jaidi to endorse its fashion products. Fadil Jaidi is expected to help strengthen consumers' memories of the M231 brand image which always revolves around elegant, casual, and modern impressions. Therefore, this study aims to prove the influence of celebrity endorser Fadil Jaidi and brand image on the purchase decision of M231 fashion products on Instagram social media. This study used data collection techniques using survey methods, and sampling techniques using purposive sampling by distributing questionnaires to 61 respondents. The results proved that celebrity endorser Fadil Jaidi had a positive and significant influence on the purchase decision of M231 fashion products on Instagram social media, brand image did not have a significant effect on the purchase decision of M231 fashion products on Instagram social media, celebrity endorser Fadil Jaidi and brand image together influence the purchase decision of M231 fashion products on Instagram social media.